The Internationalization of Chinese Firms in IT Sector - Li, Ji (2007)
The paper examines the extent to which the prevailing theories of internationalization can explain Chinese IT firms' internationalization strategies and processed. By reporting on the case studies of Lenovo and Huawei, this paper analyses each firm's motivations for internationalization and their internationalization strategies, focusing on entry mode strategy and production strategy. Consequently, this paper concludes that the motives for Chinese IT firms' internationalization are to address their competitive disadvantages, rather than exploit their competitive advantages like traditional theories assumed; and the internationalization strategies can be summarized as technology-seeking strategy so as to enhance their competitive capabilities in the global market.